Evaluating sociometer theory in children's everyday lives: Inclusion, but not exclusion by peers at school is related to within-day change in self-esteem. Issue 5 (September 2021) - Schmidt, Andrea; Dirk, Judith; Neubauer, Andreas B; Schmiedek, Florian
Sociometer theory proposes that a person's self-esteem is a permanent monitor of perceived social inclusion and exclusion in a given situation. Despite this within-person perspective, respective research in children's everyday lives is lacking. In three intensive longitudinal studies, we examined whether children's self-esteem was associated with social inclusion and exclusion by peers at school. Based on sociometer theory, we expected social inclusion to positively predict self-esteem and social exclusion to negatively predict self-esteem on within- and between-person levels. Children aged 9–12 years reported state self-esteem twice per day (morning and evening) and social inclusion and exclusion once per day for two (Study 1) and four weeks (Studies 2–3). Consistently across studies, we found that social inclusion positively predicted evening self-esteem on within- and between-person levels. By contrast, social exclusion was not associated with evening self-esteem on the within-person level. On the between-person level, social exclusion was negatively linked to evening self-esteem only in Study 1. Multilevel latent change score models revealed that children's self-esteem changed from mornings (before school) to evenings (after school) depending on their perceived daily social inclusion, but not exclusion. The findings are discussed in light of sociometer theory and the bad-is-stronger-than-good phenomenon.